Foreign Experience in Supporting the Fruit and Vegetable Growing Industry and its Possibilities for use in Uzbekistan - Israilova Khikoyat Musakulovna (Scientific Trends, 2024)
This article provides information on foreign experience in the development of the republic's agriculture, in particular, the fruit and vegetable growing industry, its economic role in the industry. In the coverage of the topic, projects implemented with the participation of national and international banks are presented with separate statistical figures.
Keywords: Agriculture, fruit and vegetable growing industry, fruit and vegetable processing, economic efficiency.